Structure-activity relationships of novel salicylaldehyde isonicotinoyl hydrazone (SIH) analogs: iron chelation, anti-oxidant and cytotoxic properties - Potůčková, Eliška; Hrušková, Kateřina; Bureš, Jan; Kovaříková, Petra; Špirková, Iva A; Pravdíková, Kateřina; Kolbabová, Lucie; Hergeselová, Tereza; Hašková, Pavlína; Jansová, Hana; Macháček, Miloslav; Jirkovská, Anna; et al. (PloS one, 2014)
Salicylaldehyde isonicotinoyl hydrazone (SIH) is a lipophilic, tridentate iron chelator with marked anti-oxidant and modest cytotoxic activity against neoplastic cells. However, it has poor stability in an aqueous environment due to the rapid hydrolysis of its hydrazone bond. In this study, we synthesized a series of new SIH analogs (based on previously described aromatic ketones with improved hydrolytic stability). Their structure-activity relationships were assessed with respect to their stability in plasma, iron chelation efficacy, redox effects and cytotoxic activity against MCF-7 breast adenocarcinoma cells. Furthermore, studies assessed the cytotoxicity of these chelators and their ability to afford protection against hydrogen peroxide-induced oxidative injury in H9c2 cardiomyoblasts. The ligands with a reduced hydrazone bond, or the presence of bulky alkyl substituents near the hydrazone bond, showed severely limited biological activity. The introduction of a bromine substituent increased ligand-induced cytotoxicity to both cancer cells and H9c2 cardiomyoblasts. A similar effect was observed when the phenolic ring was exchanged with pyridine (i.e., changing the ligating site from O, N, O to N, N, O), which led to pro-oxidative effects. In contrast, compounds with long, flexible alkyl chains adjacent to the hydrazone bond exhibited specific cytotoxic effects against MCF-7 breast adenocarcinoma cells and low toxicity against H9c2 cardiomyoblasts. Hence, this study highlights important structure-activity relationships and provides insight into the further development of aroylhydrazone iron chelators with more potent and selective anti-neoplastic effects.
Keywords: Hydrogen Peroxide; Antioxidants; buněčné linie; oxidační stres; MFC-7 buňky; Oxidative Stress; Structure-Activity Relationship; hydrazony; lidé; peroxid vodíku; Antineoplastic Agents; Iron Chelating Agents; protinádorové látky; MCF-7 Cells; Hydrazones; Cell Line; Aldehydes; myoblasty; aldehydy; antioxidancia; vztahy mezi strukturou a aktivitou; Myoblasts; chelátory železa; Humans